Analisis Faktor-Faktor Yang Mempengaruhi Pembiayaan Akad Bagi Hasil - zainatullaila . (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
This study aims to analyze factors that influence profit sharing financing or mudharabah financing. This study uses a quantitative method, where researchers only limit internal factors, namely Third Party Funds (DPK) and Non-performing Financing (NPF), and revenue-sharing. The tool used to analyze the data is using SPSS, and the results obtained. Based on the F test together with DPK variables, the revenue sharing contract and NPF for financing the profit sharing contract at Bank Muamalat Indonesia have a significant effect with Fcounting 328,097 with a significant value of 0,000. . Ftable with ? = 5%; Ftable = f ?df (n-k); (K-1); F table = (0.05; 24; 3) = 3.01 significant value 0,000 less than 0.05. F count. Ftable (328,097 3.01). These results indicate that information regarding DPK, revenue sharing contract revenue and NPF jointly influence the distribution of financing for profit sharing at Bank Muamalat Indonesia, Tbk from 2006-2012